2003
DOI: 10.1677/joe.0.1780449
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of anti-retroviral protease inhibitors on sugar transport in L6 cells

Abstract: The objective of this study was to investigate the longterm effects of anti-retroviral protease inhibitors (PIs) on 2-deoxy--glucose (2-DG) transport in L6 cells in vitro. Exposure of L6 cells to saquinavir, ritonavir, indinavir and amprenavir resulted in significant increases in 2-DG transport using PI concentrations of 1-10 µM with continual exposure to PI. After removal of the PI for up to 48 h, 2-DG transport increases did not change and remained at pre-reversal levels. These changes in 2-DG transport wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…Although the concentrations of PIs used in our current study are 2-3-fold higher as compared to free plasma concentrations observed in patients, since plasma protein binding is high for most of the PIs, the concentrations used in our in vitro study may correspond to plasma concentrations achievable. In addition, these concentrations have also been used in several other published studies (10,12,15,40). Our findings clearly indicated a drug-specific instead of a class-specific effect on the INS-1 cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although the concentrations of PIs used in our current study are 2-3-fold higher as compared to free plasma concentrations observed in patients, since plasma protein binding is high for most of the PIs, the concentrations used in our in vitro study may correspond to plasma concentrations achievable. In addition, these concentrations have also been used in several other published studies (10,12,15,40). Our findings clearly indicated a drug-specific instead of a class-specific effect on the INS-1 cells.…”
Section: Discussionsupporting
confidence: 73%
“…These clinical observations have spurred an interest in delineation of the mechanisms involved in PI-induced IRS. The mechanism of PI-induced IRS had previously been linked to suppressed insulin action on the skeletal muscle (10), adipose tissue (11) or the hepatic cells (12), but the effect of PIs on insulin secretion by the b-cells of the pancreas has not been thoroughly investigated (13). Indeed, clinical data suggests that PI-containing regimens impair glucose tolerance in HIV-1 infected patients by induction of peripheral IRS in skeletal muscle and adipose tissue and by impairment of the b-cells to compensate for the insulin resistance (14).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced skeletal glucose uptake was caused by significantly impaired glucose transport and phosphorylation; skeletal muscle glucose uptake was reduced by 66% in treated patients when compared to therapy-naive patients. Contrary to these findings obtained under insulinic stress, available preclinical data suggest that under basal conditions, HAART increases rather than decreases glucose uptake of skeletal muscle cells (21). More specifically, both saquinovir, indinavir, ritonavir and amprenavir at a concentration of 10 µM were shown to nearly double the uptake of 2-deoxyglucose of L6 myoblasts under basal conditions.…”
Section: Discussioncontrasting
confidence: 58%
“…Cell fractionation and membrane isolation. L6 cells from 150-mm diameter Petri plates (Falcon) were treated and plasma membranes prepared as previously described (20). Briefly, after homogenization with a Dounce homogenizer, a 1,000g centrifugation to remove unbroken cells and nuclei was performed.…”
mentioning
confidence: 99%